Structure guided design of a series of selective pyrrolopyrimidinone MARK inhibitors. Issue 1 (1st January 2017) - Katz, Jason D.; Haidle, Andrew; Childers, Kaleen K.; Zabierek, Anna A.; Jewell, James P.; Hou, Yongquan; Altman, Michael D.; Szewczak, Alexander; Chen, Dapeng; Harsch, Andreas; Hayashi, Mansuo; Warren, Lee; et al.
Graphical abstract: Abstract: The initial structure activity relationships around an isoindoline uHTS hit will be described. Information gleaned from ligand co-crystal structures allowed for rapid refinements in both MARK potency and kinase selectivity. These efforts allowed for the identification of a compound with properties suitable for use as an in vitro tool compound for validation studies on MARK as a viable target for Alzheimer's disease.